Impact-Linked Payments: A Model for Incentivising Service Delivery to Deaf Learners in Kenya - and Norrag
Authors: Arushi Terway, Nisha Ramachandran, Archana Mehendale The Impact-Linked Fund for Education uses Impact-Linked Payments to support eKitabu, a for-profit social enterprise, in enhancing education...
Keywords: Org:eKitabu